The Impact of Child Injury Prevention Package (CIPP) on Injury Prevention in Toddler - Hastuti, Retno Puji; Musiana, Musiana (Poltekkes Kemenkes Tanjung Karang, 2024)
Injuries are a cause of morbidity and mortality in children under five. In Indonesia, the prevalence of injuries to children under five in 2013 was 8.5%, and in 2018, it was 8.2%. Injuries to toddlers derive from not-yet-optimal levels of development, high curiosity, lack of gross motor coordination, and the ability to anticipate danger. Nurses can provide anticipatory guidance to parents to increase parental understanding and prevent injuries to toddlers. The research aimed to determine the effect of CIPP on injury prevention in toddlers. The research method used the One group pre and post-test design with the population of all toddlers in the Puskesmas (Community Health Centre) Rajabasa Indah working area. The research sample using Proportional Random Sampling was 120 parents of toddlers. Data collection was done through interviews using screening cards. Data were analyzed using proportions and a T-test. The results of toddler characteristics were male (55.83%), toddler (55.83%), and standard nutritional status (70.8%). The proportion of toddlers who experienced injuries was 41.66%, and the most frequently experienced injuries were falls (37.5%). There was a significant difference in the mean value of knowledge about injury prevention in toddlers (p-value=0.000), environmental modification (p-value=0.000), and injury incidences in toddlers (p-value=0.000) before and after the anticipatory guidance intervention using CIPP. It is recommended to integrate CIPP into toddler health promotion, socialize CIPP with parents, cadres and kindergarten teachers, and develop CIPP-Android based applications.